The Relationship Of Antibiotic Rationality To Clinical Outcomes In Adult UTI Patients Using The Gyssens Method At The Inpatient Unit Of PKU Muhammadiyah Hospital, Surakarta - Nabilla Aulia Khorifatunnisa; Aprilia Puteri Santika; Annie Rahmatillah (CV. AFDIFAL MAJU BERKAH, 2026)
Urinary Tract Infection (UTI) is a common infection with a high risk of antibiotic resistance due to irrational use. This study evaluated the rationality of antibiotics on the clinical outcomes of adult UTI patients using the Gyssens method at PKU Muhammadiyah Surakarta Hospital. To analyze the profile, rationality of antibiotics, and their relationship with clinical improvement. Retrospective descriptive study on 77 adult UTI inpatients from January to December 2024, purposive sampling, medical record instruments, Gyssens and Chi-Square analysis (SPSS 25). Rationality 53.25% (category 0), Cefuroxime most (38.96%), normal leukocytes 92.2%, p = 0.006 indicating a significant relationship between rationality and clinical improvement. Rational use of antibiotics significantly improves the clinical outcomes of UTI, supporting antimicrobial stewardship.